Unveiling patterns of viral pathogen infection in free-ranging carnivores of northern Portugal using a complementary methodological approach. (April 2020) - Rosa, Gonçalo M.; Santos, Nuno; Grøndahl-Rosado, Ricardo; Fonseca, Francisco Petrucci; Tavares, Luis; Neto, Isabel; Cartaxeiro, Clara; Duarte, Ana
Highlights: CDV, CPV and CCoV nucleic acids were detected in samples from Portuguese wild carnivores. Exposure to Canine parvovirus and Canine distemper virus was confirmed by serology. Sample conservation status was significant for antibody detection. Co-infections by multiple pathogens (two or three viruses) were recorded. Abstract: Pathogen surveillance in free-ranging carnivores presents challenges due to their low densitie and secretive nature. We combined molecular and serological assays to investigate infections by viral pathogens (Canine parvovirus (CPV), Canine distemper virus (CDV) and Canine coronavirus (CCoV)) in Portuguese carnivores (Canis lupus, Vulpes vulpes, Lutra lutra, Martes foina, M. martes, Meles meles, and Genetta genetta) over a period of 16 years. Additionally we explored spatio-temporal patterns of virus occurrence in Canis lupus. Our study identified CPV DNA in all carnivore species with an overall prevalence of 91.9 %. CPV was detected in all sampled years and seasons in Canis lupus, supporting its enzootic nature. CDV RNA was mainly detected in the Canidae family, with viral nucleic acid recorded between 2005 and 2008 with a peak prevalence of 67 % among the wolf population, followed by a sharp decline, suggesting an epizootic behaviour of the virus. Antibodies show that mustelids and viverrids were often exposed to CDV. CCoV was first recorded by molecular methods in wolf samples in 2002, remaining in the wolf populations with marked fluctuations over time. The dual serological and molecular approach provided important epidemiological data on pathogens of wild carnivores in Portugal. These programmes should also include monitoring of other potential reservoir hosts such as domestic cats and dogs.